2022
DOI: 10.3390/su14063630
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus among Energy Consumption, Economic Growth and Trade Openness: Evidence from West Africa

Abstract: The West African region has experienced high economic development. With the increasing energy consumption and emissions, how to coordinate the relationship among energy consumption, trade opening, and economic growth, and how to develop a low-carbon development pattern are becoming the most important issues in West Africa. This paper uses the tri-variable Toda-Yamamoto model to investigate the dynamic interactions among energy consumption, economic growth, and trade in West Africa. The findings indicate that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…The expansion of economic scale increases the output of products, whereas the expansion of output may increase CEs at the same technological level. When economic growth reaches a certain stage, that is, after the turning point of the EKC, the expansion of the economic scale may lead to a reduction in CE changes in the technology level and production model [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The expansion of economic scale increases the output of products, whereas the expansion of output may increase CEs at the same technological level. When economic growth reaches a certain stage, that is, after the turning point of the EKC, the expansion of the economic scale may lead to a reduction in CE changes in the technology level and production model [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the other variables are insignificant in the short run. In the long run, energy consumption and economic growth both significantly and positively impact CO2 emissions (Anwar & Elfaki, 2021;Muhammad, 2019;Qi et al, 2022;Wen et al, 2021). If energy consumption is increased by one percent it will increase CO2 emission by 0.0126 percent.…”
Section: Results Of Ardl Modelmentioning
confidence: 99%
“…Most empirical literatures are dominated by conflicting evidences with respect to the nature of the relationship between energy consumption and growth. For instance, the recent work of [17], which investigated the dynamic interactions among energy consumption, economic growth, and trade in West Africa using the tri-variable Toda-Yamamoto model, has demonstrated that the positive impact of energy consumption on economic growth in West Africa showed a significant lag effect, and that energy consumption has a strong trade-dependent relationship to economic promotion, while trade opening and economic growth in West Africa were mutually reinforcing in the long run. [18] Documented that increased in crude oil price significantly led to a rise in energy consumption while Co2 emissions exert negatively on growth in Venezuela, after investigating oil price, energy consumption and carbon dioxide emissions using ARDL approach.…”
Section: Empirical Reviewmentioning
confidence: 99%